LncRNA BACE1-AS delays the propagation of Cryptosporidium parvum through regulating cell apoptosis by targeting the miR-6805-5p/IRF3 axis - Shuang Huang; Xin Yang; Ting-Li Liu; Gui-Rong Hu; Qian Yao; Jun-Ke Song; Ying-Ying Fan; Guang-Hui Zhao (Microbiology Spectrum)
ABSTRACT Cryptosporidium spp. are important zoonotic pathogens causing diarrhea in humans and various animals. To date, there are still no effective drugs and vaccines for the prevention and treatment of cryptosporidiosis, mainly due to the absence of knowledge on the interaction mechanisms between hosts and Cryptosporidium. Increasing evidence has indicated that long non-coding RNAs (lncRNAs) play significant roles in various physiological and pathological processes. Our previous study showed that Cryptosporidium parvum infection induced significant differential changes in lncRNA expression profiles in HCT-8 cells. BACE1-AS was a significantly downregulated lncRNA in HCT-8 cells during C. parvum infection, but its roles were still unknown. Results of the present study indicated that C. parvum infection significantly downregulated the expression of BACE1-AS probably through regulating the nuclear factor kappa-B (NF-κB) signaling pathway, and the expression of BACE1-AS was negatively related to the propagation of C. parvum in HCT-8 cells. BACE1-AS was mainly localized outside of the nucleus of HCT-8 cells and promoted the expression of IRF3 by sponging miR-6805-5p during C. parvum infection. Further studies indicated that the BACE1-AS/miR-6805-5p/IRF3 axis delayed in vitro propagation of C. parvum through regulating BCL2-mediated apoptosis of HCT-8 cells. The present study enriches our knowledge on the function of host lncRNAs during Cryptosporidium infection and contributes to our understanding of the interaction between hosts and Cryptosporidium.IMPORTANCERecent studies indicate that Cryptosporidium can regulate cell apoptosis to promote its development in host cells, but the mechanism is still unclear. This study identified a significantly downregulated host lncRNA BACE1-AS during C. parvum infection, which could regulate cell apoptosis to affect the propagation of C. parvum in vitro by targeting the miR-6805-5p/IRF3 axis. The present study contributes to our understanding of the pathogenesis of Cryptosporidium and provides potential targets for the development of drugs and vaccines against cryptosporidiosis.